Un enfoque etnomatemático de la modelación a través de la Etnomodelación - Rosa, Milton (2019)
It is important to seek for alternative methodological approaches, while western mathematical practices are accepted worldwide to record historical forms of mathematical ideas and procedures that occur in diﬀ erent cultural contexts. An alternative methodological approach is ethnomodelling, which we consider as the practical application of ethnomathematics that adds the cultural perspective to the concepts of mathematical modelling. In this context, sophisticated mathematical ideas and practices, including geometric principles in craftwork, architectural concepts and practices, are found in activities and artifacts of many local and global cultures. Th ese concepts are related to numerical relationships found in measurement, calculation, games, divination, navigation, astronomy, modelling and in a wide variety of other mathematical procedures, as well as in cultural artifacts, through the development of ethnomodellin